The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2006
DOI: 10.1167/iovs.05-0945
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Betaxolol in Ocular Tissues of Patients with Glaucoma and Normal Monkeys after 1 Month of Topical Ocular Administration

Abstract: Topically applied betaxolol was bioavailable to posterior ocular tissues, including the retina and optic nerve head, of patients with glaucoma and of normal cynomolgus monkeys. The higher betaxolol levels in the treated versus untreated monkey eyes are consistent with betaxolol's reaching posterior tissues by local absorption and distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 18 publications
1
24
0
Order By: Relevance
“…In our single dose study, dorzolamide showed significantly higher delivery (both AUC and C max ) to the vitreous and optic nerve than that of brinzolamide. Optic nerve levels of dorzolamide and brinzolamide were significantly higher than those of the vitreous and posterior retina, which is consistent with a previously published report for betaxolol (Holló et al, 2006). Maurice (2002) suggested that drug entry into the retrobulbar space via the conjunctival pathway contributes toward optic nerve drug delivery.…”
Section: Ocular Pharmacokinetics Of Dorzolamide and Brinzolamidesupporting
confidence: 91%
See 1 more Smart Citation
“…In our single dose study, dorzolamide showed significantly higher delivery (both AUC and C max ) to the vitreous and optic nerve than that of brinzolamide. Optic nerve levels of dorzolamide and brinzolamide were significantly higher than those of the vitreous and posterior retina, which is consistent with a previously published report for betaxolol (Holló et al, 2006). Maurice (2002) suggested that drug entry into the retrobulbar space via the conjunctival pathway contributes toward optic nerve drug delivery.…”
Section: Ocular Pharmacokinetics Of Dorzolamide and Brinzolamidesupporting
confidence: 91%
“…Furthermore, the nipradilol levels in the periocular tissue around the equator region were 8.6-fold higher than those in the periocular tissue near the optic nerve. Furthermore, Holló et al (2006) also showed that after topical application of betaxolol in Cynomolgus monkey, drug levels in the anterior part were significantly higher than those in the posterior part of the back of the eye. Such regional differences in the tissue distribution after topical administration might be because the conjunctiva covers only the anterior part of the globe and makes an intimate contact with the sclera in this region, allowing ready exposure of the drug to the sclera and underlying tissues in the anterior part of the globe.…”
Section: Ocular Pharmacokinetics Of Dorzolamide and Brinzolamidementioning
confidence: 92%
“…On the other hand, using HPLC and tandem MS, the local tissue absorption and distribution of topical administration of betaxolol in both glaucoma patients and normal monkeys were investigated. A significant dose was observed at the posterior of the eyes, which provided evidence for an efficient delivery of drug 155 …”
Section: Applications Of Proteomic Researchmentioning
confidence: 88%
“…In terms of betaxolol, however, topical application of 25 µg / ml suspension for 28 -30 days to monkeys and human eyes resulted in the local concentration reaching approximately 0.1 to 0.4 µM in retina and optic nerve head, an estimation based on the assumption that betaxolol is evenly distributed throughout the retina (33). If this is the case, the blocking effects of betaxolol to not only NMDA receptors but also Ca 2+ and Na + channels are unlikely to be produced.…”
Section: Discussionmentioning
confidence: 99%